Implementation of the National Insight Education Program at the Ummul Quro Al-Islami Bogor Student Islamic Boarding School - Wawar Suwardi Kuba; Budi Handrianto; Ahmad Idhofi (al-Afkar, Journal For Islamic Studies, 2024)
Student Islamic boarding schools have a crucial role in shaping the character and national identity of the younger generation. One of the programs implemented in student Islamic boarding schools is the national insight program. This research aims to determine the extent of the implementation of the national insight education program at the Ummul Quro Al-Islami Institute (IUQI) Bogor student Islamic boarding school. This research uses descriptive-qualitative methodology. Data collection techniques in this research are documentation, observation, and interviews. The national insight education program at the Bogor Ummul Quro Al-Islami Institute (IUQI) student Islamic boarding school is implemented in the study of religious moderation, field practice, community service and arts and culture activities.